Low back pain and associated factors among users of community health centres in South Africa : a prevalence study - Major-Helsloot, Mel (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScPhysio (Interdisciplinary Health Sciences. Physiotherapy))--University of Stellenobosch, 2010.